Lithium supplement agent and preparation method thereof

C@Fe3O4 nanocrystals were synthesized by controlling the pH value of the carbon source dispersion, and then mixed and sintered with LiOH·H2O and Al2O3 to form C@Li5FeO4 lithium supplement, which solved the problems of large particle size and poor conductivity of Li5FeO4 material and improved the first charge-discharge efficiency and cycle stability of lithium-ion batteries.

CN120914255AActive Publication Date: 2025-11-07JIANGXI INSPIRE NANO MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510966910.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-11-07
Estimated Expiration
2045-07-14

AI Technical Summary

Technical Problem

The existing Li5FeO4 material has an excessively large particle size and poor conductivity, which leads to a severe loss of specific capacity in the first cycle of lithium-ion batteries, thus limiting the improvement of the energy density of lithium-ion batteries.

Method used

By controlling the pH value of the carbon source dispersion through the preparation method, C@Fe3O4 nanocrystals were synthesized. Subsequently, they were mixed with micron-sized LiOH·H2O and nano-sized Al2O3, and subjected to two sintering and pulverization processes. A stabilizer was added to form C@Li5FeO4 lithium supplement, ensuring the uniformity of material particles and conductivity.

Benefits of technology

It improves the initial charge-discharge efficiency of lithium iron phosphate batteries, enhances the overall performance of lithium-ion batteries, achieves an initial coulombic efficiency of over 99%, and has no substantial impact on discharge capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914255A_ABST
    Figure CN120914255A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium supplement agent and a preparation method thereof.The preparation method of the lithium supplement agent comprises the following steps that (1) carbon source dispersion liquid is prepared, the carbon source dispersion liquid comprises a dispersing agent, a nano carbon material and water, and the pH value of the carbon source dispersion liquid is adjusted to be 12-13; (2) simultaneously dropwise adding an iron-containing solution and an alkaline solution into the carbon source dispersion liquid under the condition of keeping the temperature of the carbon source dispersion liquid at 40-60 DEG C, controlling the pH value of the system, and after dropwise adding, standing, removing impurities and drying to obtain C-coated Fe3O4; (3) uniformly mixing C-coated Fe3O4, micron-sized LiOH.H2O and nano-sized Al2O3 to obtain a mixture, taking the mixture as a precursor, and sequentially sintering and crushing the precursor twice to obtain primary powder; and (4) adding a stabilizer into the primary powder, uniformly mixing, sintering and crushing to obtain the lithium supplement agent. The lithium supplement agent can improve the first charge-discharge efficiency of the lithium iron phosphate battery, and does not cause substantial influence on the discharge capacity and the cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lithium ion batteries, in particular to a lithium supplementing agent and a preparation method thereof. BACKGROUND

[0002] During the first charging process of lithium ion batteries, a solid electrolyte interface film (SEI film) is formed on the surface of the negative electrode, which will irreversibly consume active lithium in the positive electrode material, and further cause the loss of specific capacity during the first cycle of the battery. The irreversible capacity loss rate of the most widely used commercial graphite negative electrode material is about 10%; while for silicon-based and tin-based negative electrode materials with higher theoretical specific capacity, this loss rate can even exceed 30%, which seriously restricts the improvement of the energy density of lithium ion batteries. To address this problem, lithium supplementing technology has shown important application value and research significance because it can effectively compensate for the irreversible capacity loss and restore the reversible capacity of the positive electrode material.

[0003] Existing lithium supplementing technologies are mainly divided into positive electrode lithium supplementing and negative electrode lithium supplementing, among which, the positive electrode lithium supplementing technology has more application advantages due to its simple process and strong environmental adaptability. This technology introduces a high-capacity lithium supplementing additive during the preparation of the positive electrode slurry, so that the additive material can release excess lithium ions to compensate for the capacity loss during the subsequent charging process. Among many positive electrode lithium supplementing additives, Li5FeO4 has attracted much attention due to its excellent theoretical performance: 1) extremely high lithium storage capacity (5 Li + per mole of Li5FeO4); 2) outstanding specific capacity (up to 867 mAh / g).

[0004] Studies have shown that the incorporation of an appropriate amount of Li5FeO4 into conventional positive electrode materials can significantly improve the first coulombic efficiency and overall energy density of lithium ion batteries. However, existing Li5FeO4 materials still face problems such as excessively large particle size and unsatisfactory electrical conductivity. SUMMARY

[0005] The present application provides a preparation method of a lithium supplementing agent, which can improve the first charge-discharge efficiency of lithium iron phosphate batteries, while not substantially affecting the discharge capacity and cycle stability, and improve the overall performance of lithium ion batteries.

[0006] A preparation method of a lithium supplementing agent, comprising the following steps:

[0007] (1) configuring a carbon source dispersion liquid, the carbon source dispersion liquid comprising a dispersing agent, a nano-carbon material and water, and adjusting the pH value of the carbon source dispersion liquid to 12-13;

[0008] (2) under the condition that the temperature of the carbon source dispersion liquid is maintained at 40-60℃, the iron-containing solution and the alkaline solution are simultaneously added dropwise into the carbon source dispersion liquid, when the volume of the consumed alkaline solution accounts for 55%-65% of the total volume of the alkaline solution, the pH is adjusted to 10-11 by using the iron-containing solution and the alkaline solution, the iron-containing solution and the alkaline solution are continuously added dropwise, after the addition is completed, impurities are removed and dried to obtain C@Fe3O4;

[0009] (3) C@Fe3O4, micron-sized LiOH·H2O and nano-sized Al2O3 are uniformly mixed to serve as a precursor, the precursor is subjected to two times of sintering and crushing in sequence under the condition of nitrogen protection to obtain a primary powder;

[0010] (4) a stabilizer is added into the primary powder, the mixture is uniformly mixed and then sintered and crushed to obtain the lithium supplement agent.

[0011] The following also provides several optional modes, but not as an additional limitation to the above general scheme, only further supplement or preferred, without technical or logical contradiction, each optional mode can be combined with the above general scheme, and can also be combined between multiple optional modes.

[0012] In the present application, C@Fe3O4 is a crystal particle formed by the mutual combination of carbon material and Fe3O4, the C@Fe3O4 material has uniform particles, the size is about 80-150 nm, the specific surface area is high, and the electrical conductivity is good, the lithium supplement effect of the lithium supplement agent prepared by using the C@Fe3O4 material is good, and the first coulomb efficiency of the lithium iron phosphate battery added with the lithium supplement agent reaches more than 99%.

[0013] The dispersant is at least one of polyvinylpyrrolidone, sodium carboxymethyl cellulose, polymaleic anhydride, polystyrene sulfonic acid sodium, and naphthalene sulfonate sodium salt. The dispersant is a water-soluble substance and can be dissolved in water to form a solution.

[0014] The nano-carbon material is at least one of carbon black, carbon nanotube, porous carbon and graphene, the nano-carbon material is mixed with the dispersant in the form of aqueous slurry, and the content of the nano-carbon material in the aqueous slurry is 20-30%. The nano-carbon material is mixed with the dispersant in the form of aqueous slurry, and diluted by water to obtain a carbon source dispersion liquid.

[0015] The carbon source dispersion liquid is maintained at a temperature of 40-60℃ by using an oil bath, and the carbon source dispersion liquid is kept in a state of continuous stirring during the addition of the iron-containing solution and the alkaline solution, that is, the system is always stirred to mix the substances uniformly during the addition of the iron-containing solution and the alkaline solution, and nitrogen is introduced for protection during the mixing process.

[0016] The pH value is crucial in the process of C@Fe3O4 crystal growth, the iron-containing solution and the alkaline solution are added dropwise into the carbon source dispersion liquid, the pH value of the iron-containing solution is acidic, and the pH value of the alkaline solution is alkaline, and the pH value of the carbon source dispersion liquid system can be adjusted by using the iron-containing solution and the alkaline solution.

[0017] The pH value control in the application is divided into two stages, in the early stage of the reaction, the pH value is controlled to be alkaline, that is, the pH value is 12-13, and in the later stage of the reaction, the pH value is reduced and controlled to be 10-11, the dividing point between the early stage of the reaction and the later stage of the reaction is that the volume of the consumed alkaline solution accounts for 55%-65% of the total volume of the alkaline solution, for example, the total volume of the alkaline solution added dropwise into the carbon source dispersion liquid is 200 mL, the pH value is adjusted in the interval of 110 mL-130 mL, before the pH value, it is the early stage of the reaction, and after the pH value is adjusted, it is the later stage of the reaction.

[0018] In the whole process before and after the pH value is adjusted to 10-11, the dropwise adding speed ratio of the iron-containing solution and the alkaline solution is controlled, so that the pH value of the system does not change sharply during the dropwise adding process, and can be stabilized around a certain pH value. Controlling the pH value in the early stage and the later stage of the reaction can make the crystal particles smaller, more uniform and the particle boundary clearer.

[0019] C@Li5FeO4 is formed by combining Li with C@Fe3O4, and the particle size thereof depends on the particle size of the C@Fe3O4 crystal, the particle size and uniformity of the C@Fe3O4 crystal will affect the particle size and uniformity of the C@Li5FeO4, smaller crystal size means larger specific surface area, which can improve the efficiency of catalytic reaction, increase the reaction activity and catalytic activity of the material, and help to improve the electronic conductivity and ion diffusion rate, and uniform particle distribution can help to improve the cycle stability and safety of the battery.

[0020] The standing after the dropwise adding is used to promote the aging of the crystal, the standing time is 2-3 hours, after the standing is completed, at least two times of filtration cleaning are carried out by using 1 mol / L NaOH aqueous solution to remove possible sulfides, then hot water at 70℃ is used to further remove the residual impurities such as sulfur and sodium by a large amount of water washing and suction filtration, and then it is placed in a blast drying oven for drying for 24 hours to obtain C@Fe3O4.

[0021] The stabilizer is bitumen micro powder or phenolic resin micro powder, the introduction of the stabilizer can promote the uniform distribution of the carbon source on the surface of the material, form a uniform carbon coating layer, and thus optimize the phase composition and electrochemical performance of the product C@Fe3O4, so that it can play a greater role in lithium supplement application.

[0022] High-purity nitrogen is introduced during sintering to ensure that the oxygen content is less than 1 ppm, ensuring that the preparation process of C@Li5FeO4 is carried out in an oxygen-free environment, thereby obtaining better material performance.

[0023] Optionally, the mass fraction of the dispersant in the carbon source dispersion liquid is 0.05-0.5%, and the carbon content is 1.1%-1.5%. Optionally, the mass fraction of the dispersant in the carbon source dispersion liquid is 0.2-0.5%, and the carbon content is 1.1%-1.5%.

[0024] The carbon content in the carbon source dispersion liquid is crucial for the consistency and stability of the subsequent synthesis of C@Fe3O4 nanocrystalline particles, and precise carbon content control helps to control the growth of nanoparticles, thereby optimizing their electrochemical performance.

[0025] The carbon content in the carbon source dispersion liquid also has a significant impact on multiple properties of the lithium supplement agent. Suitable carbon wrapping can effectively disperse the particles and prevent them from agglomerating, thereby increasing the specific surface area of the material, promoting the transfer of electric charges and the diffusion of ions, and improving the charge and discharge performance of the material. Meanwhile, the carbon layer acts as a protective layer, which can alleviate the volume change of the material and enhance the structural stability.

[0026] The solute of the iron-containing solution is at least one of iron sulfate, iron nitrate, and iron chloride, and the solute of the alkaline solution is at least one of sodium hydroxide, ammonia, and calcium hydroxide. The solvent of the iron-containing solution and the alkaline solution is water. The solute of the iron-containing solution is a water-soluble iron salt. After dissolving each iron salt in water, an iron ion-containing solution is formed, which is the iron-containing solution. The solute of the alkaline solution is various alkaline substances. After dissolving them in water, an alkaline solution is formed. The carbon source dispersion liquid is added simultaneously with the iron-containing solution and the alkaline solution to provide a growth environment for C@Fe3O4.

[0027] The particle size D 50 of the micron-sized LiOH·H2O is less than 20 μm, and the average particle size of the nanoscale Al2O3 is less than 150 nm.

[0028] Optionally, the molar concentration of the iron-containing solution is 1-3 mol / L, and the molar concentration of the alkaline solution is 1-3 mol / L.

[0029] Optionally, the molar concentration of the iron-containing solution is the same as that of the alkaline solution.

[0030] Optionally, the volume ratio of the carbon source dispersion liquid, the iron-containing solution, and the alkaline solution is 3-10:100:150-280.

[0031] Optionally, the volume ratio of the carbon source dispersion liquid, the iron-containing solution, and the alkaline solution is 4-6:100:180-220.

[0032] Optionally, the iron-containing solution is an aqueous solution of FeSO4·7H2O, and the alkaline solution is an aqueous solution of NaOH. The molar concentration of the aqueous solution of FeSO4·7H2O is 1-3 mol / L, and the molar concentration of the aqueous solution of NaOH is 1-3 mol / L. During the entire dropping process, the dropping speed ratio of the aqueous solution of FeSO4·7H2O to the aqueous solution of NaOH is 1:2-2.1. The dropping speed of the aqueous solution of FeSO4·7H2O is 4-6 mL / min, and the dropping speed of the aqueous solution of NaOH is 8-12 mL / min.

[0033] Optionally, in the precursor, the molar ratio of Fe in C@Fe3O4 to Li in micro-sized LiOH·H2O is 1:5-5.5; and in the precursor, the addition amount of nano-sized Al2O3 is 0.05-0.1%.

[0034] Optionally, the temperature of the two sintering processes performed on the precursor in sequence is 400-800℃, and the sintering time is 20-32 hours.

[0035] Optionally, the temperature of the two sintering processes performed on the precursor in sequence is 480-550℃.

[0036] Optionally, the stabilizer is in powder form, and the material of the stabilizer is at least one of pitch, phenolic resin, polyethylene glycol resin, needle coke, and glucose. After the stabilizer is introduced, the sintering temperature is 350℃, and the sintering time is 20-24 hours.

[0037] The D50 of the stabilizer is 0.2-5 μm, and preferably 0.2-2 μm. 50 The D50 of the stabilizer is 0.2-5 μm, and preferably 0.2-2 μm.

[0038] The application also provides a lithium supplementing agent prepared by the preparation method.

[0039] The application also provides a lithium ion battery positive electrode material to which the lithium supplementing agent is added. The lithium ion battery positive electrode material contains lithium iron phosphate. Based on the lithium iron phosphate, the addition amount of the lithium supplementing agent is 2-4 wt%.

[0040] The lithium supplementing agent provided by the application can improve the first charge-discharge efficiency of a lithium iron phosphate battery, while not substantially affecting the discharge capacity and cycle stability, thereby improving the comprehensive performance of the lithium ion battery. BRIEF DESCRIPTION OF DRAWINGS

[0041] Figure 1 A flowchart for preparing the lithium supplementing agent is shown in FIG. 1.

[0042] Figure 2 A flowchart for preparing C@Fe3O4 is shown in FIG. 2.

[0043] The lithium supplementing agent provided by the application can improve the first charge-discharge efficiency of a lithium iron phosphate battery, while not substantially affecting the discharge capacity and cycle stability, thereby improving the comprehensive performance of the lithium ion battery.Figure 3 SEM image of C@Fe3O4 prepared for Example 1;

[0044] Figure 4 SEM image of C@Li5FeO4 prepared for Example 1;

[0045] Figure 5 Initial charge-discharge curves of LFP and LFP(LFO) obtained from performance test in Example 1;

[0046] Figure 6 SEM image of C@Fe3O4 prepared for Examples 2-5;

[0047] Figure 7 SEM image of C@Fe3O4 prepared for Examples 6-11;

[0048] Figure 8 SEM image of C@Fe3O4 prepared for Examples 12-15;

[0049] Figure 9 SEM image of C@Fe3O4 prepared for Examples 16-20;

[0050] Figure 10 XRD pattern of C@Li5FeO4 prepared for Comparative Example 3 and Example 23;

[0051] Figure 11 Electrochemical impedance spectrogram (EIS) of half-cell using C@Li5FeO4 and half-cell not using C@Li5FeO4. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of protection of the present application.

[0053] In order to better describe and illustrate the embodiments of the present application, one or more drawings can be referred to, but additional details or examples used to describe the drawings should not be considered as limiting the scope of any one of the invention, the presently described embodiments or the preferred modes of the present application.

[0054] It should be noted that when a component is referred to as being "connected" with another component, it can be directly connected with the other component or there can be a middle component. When a component is referred to as being "disposed on" another component, it can be directly disposed on the other component or there can be a middle component.

[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in the description herein is for describing particular embodiments only and is not intended to be limiting of the application.

[0056] Example 1

[0057] A method for preparing a lithium supplement agent is described in Figure 1 as shown, comprising the following steps:

[0058] I. Preparation of C@Fe3O4, the process is described in Figure 2 as shown, specifically comprising the following steps:

[0059] (1) Preparation of carbon source dispersion solution mother liquor: take 1.87g carbon black dispersion solution (the carbon black content in the carbon black dispersion solution is 25%), add 2.27g water, and then add 0.05g polyvinylpyrrolidone (i.e. dispersant), stir uniformly to obtain the carbon source dispersion solution mother liquor, in which the mass fraction of carbon black is 11.15% and the mass fraction of polyvinylpyrrolidone is 1%;

[0060] (2) In a 500mL three-necked flask equipped with a magnetic stirrer and a dropping funnel, add 0.50g carbon source dispersion solution mother liquor and 5g water, and stir at a stirring speed of 500rmp to obtain the carbon source dispersion solution, which is heated in an oil bath at 50℃ while being protected by nitrogen gas, and ammonia water is added dropwise to adjust the pH value, so that the pH value is maintained at 12.

[0061] (3) Take 55.6g FeSO4·7H2O and dissolve it in 100g deionized water to prepare a FeSO4·7H2O aqueous solution, the molar concentration of which is 2mol / L. Take 16g NaOH and dissolve it in 200g deionized water to prepare a NaOH aqueous solution, the molar concentration of which is 2mol / L.

[0062] FeSO4·7H2O aqueous solution and NaOH aqueous solution are simultaneously added dropwise into the carbon source dispersion solution, and the pH value is adjusted to 12.6 (i.e. the pH value in the early stage of the reaction) using the FeSO4·7H2O aqueous solution and NaOH aqueous solution, the FeSO4·7H2O aqueous solution and NaOH aqueous solution are continuously added dropwise, and when the consumption volume of the NaOH aqueous solution is 120mL (this volume includes the volume consumed during pH adjustment), the pH value is adjusted to 10.2 (i.e. the pH value in the late stage of the reaction), and the FeSO4·7H2O aqueous solution and NaOH aqueous solution are continuously added dropwise.

[0063] The dropping speed of FeSO4·7H2O aqueous solution is 5 mL / min and the dropping speed of NaOH aqueous solution is 10 mL / min except for the pH adjustment.

[0064] (4) After the dropping is completed, the mixed solution is left for 3 hours, and then is washed twice by filtration using 1 mol / L NaOH aqueous solution to remove possible sulfides. Then, hot water at 70℃ is used to further remove residual sulfur, sodium and other impurities by means of a large amount of water washing and suction filtration. Subsequently, the material is placed in a blast drying oven for drying for 24 hours to obtain C@Fe3O4.

[0065] The appearance of C@Fe3O4 is yellow-black powder, the content of Fe element is 68%, the content of carbon element is 4%, and the content of S element and Na element is both 2000 ppm.

[0066] The SEM image of C@Fe3O4 is shown in Figure 3 It can be seen from the SEM image that the synthesized nanoparticles have small size, uniform distribution and clear crystal structure.

[0067] II. Preparation of C@Li5FeO4

[0068] (1) 11.628 g of LiOH·H2O (micropowder, particle size D 50 less than 20 μm), 1 g of C@Fe3O4 as a reaction raw material, and 0.008 g of nano-sized Al2O3 (average particle size less than 150 nm) as an additive are introduced to form a uniform precursor by high-speed mixing.

[0069] (2) The prepared precursor is placed in a high-temperature vacuum tube furnace for high-temperature sintering under an inert atmosphere. The first sintering temperature is 500℃, and the sintering time is 24 h. After the first sintering, the material is crushed, and then the second sintering is performed. The second sintering temperature is 490℃, and the sintering time is 20 h. The material is crushed again to obtain a powder.

[0070] (3) 0.01 g of pitch micropowder (D 50 particle size 1 μm) is added to the powder as a stabilizer, and the mixture is uniformly mixed and sintered at 350℃ for 20 h, and then crushed to remove magnetism to obtain C@Li5FeO4, i.e. a lithium supplement. The SEM image of C@Li5FeO4 is shown in Figure 4 .

[0071] Performance test of C@Li5FeO4: C@Li5FeO4 was added into the electrode prepared from lithium iron phosphate (LFP), conductive agent acetylene black, polyvinylidene fluoride (PVDF) with a mass ratio of 8:1:1, and the amount of C@Li5FeO4 added was 3 wt% of the lithium iron phosphate, with lithium sheet as the negative electrode, and a half battery was assembled and tested at 0.1C.

[0072] Referring to Figure 5 As shown in the figure, the initial charge capacity of the half battery using C@Li5FeO4 is higher than that of the half battery without C@Li5FeO4, and the first coulombic efficiency of 99.0% of the half battery using C@Li5FeO4 is also higher than that of 98.3% of the half battery without C@Li5FeO4, Figure 5 LFP (LFO) in the figure is the curve of the half battery using C@Li5FeO4, and LFP is the curve of the half battery without C@Li5FeO4.

[0073] C@Li5FeO4 can produce a pre-lithiation effect on the cathode of the half battery, providing additional irreversible capacity, effectively compensating for the lithium consumption caused by the SEI film, and the discharge capacities of the two half batteries are similar, indicating that the addition of C@Li5FeO4 does not have a significant negative impact on the discharge capacity of the positive electrode.

[0074] Referring to Figure 11 As shown in the figure, the electrochemical impedance spectroscopy (EIS) of the half battery using C@Li5FeO4 and the half battery without C@Li5FeO4, although the electronic conductivity of the half battery using C@Li5FeO4 is not high, its ionic conductivity is good. In the high frequency region of the EIS spectrum, the observed semicircular shape is mainly caused by the charge transfer resistance at the electrode interface, while in the low frequency region, the slope of the straight line part reflects the impedance of the lithium ion diffusion process. Although the half battery using C@Li5FeO4 causes a slight increase in the charge transfer resistance of the electrode interface, at the same time, the diffusion impedance of lithium ions is reduced, which can be confirmed from the change in the slope in the low frequency region. Although the overall impedance change is not significant, this indicates that the addition of C@Li5FeO4 does not adversely affect the cycle stability of the battery.

[0075] Examples 2-20

[0076] Table 1

[0077]

[0078]

[0079] In Examples 2-20, the experimental conditions were the same as in Example 1, except for the pH values ​​at the beginning and end of the reaction. Examples 2-20 mainly compared the effects of different pH values ​​at the beginning and end of the reaction on the morphology of C@Fe3O4 crystal particles.

[0080] Examples 2-5 investigated the effect of pH values ​​of 9-13 on the morphology of C@Fe3O4 crystal particles during the early stage of the reaction. (See also...) Figure 6 As shown, (a1) and (a2) are SEM images of C@Fe3O4 crystal particles from Example 2, (b1) and (b2) are SEM images of C@Fe3O4 crystal particles from Example 3, (c1) and (c2) are SEM images of C@Fe3O4 crystal particles from Example 4, and (d1) and (d2) are SEM images of C@Fe3O4 crystal particles from Example 5. Figure 6 It can be seen that within the pH range of 12 to 13, C@Fe3O4 crystal particles exhibit a smaller size (approximately 0.1 to 0.3 μm), a more uniform distribution, and clearer crystal boundaries.

[0081] Examples 6-11 investigated the effect of more precise pH control (between 12 and 13) on the morphology of C@Fe3O4 crystals during the early stage of the reaction. (See also...) Figure 7 As shown, (a) is a SEM image of C@Fe3O4 crystal particles from Example 6, (b) is a SEM image of C@Fe3O4 crystal particles from Example 7, (c) is a SEM image of C@Fe3O4 crystal particles from Example 8, (d) is a SEM image of C@Fe3O4 crystal particles from Example 9, (e) is a SEM image of C@Fe3O4 crystal particles from Example 10, and (f) is a SEM image of C@Fe3O4 crystal particles from Example 11. Figure 7 It can be seen that when the pH value is precisely controlled at approximately 12.6 in the early stage of the reaction, the synthesized crystal particles exhibit optimal characteristics in terms of size miniaturization, uniform distribution, and clarity of crystal structure.

[0082] Examples 12-15 investigated the effect of pH 8-11 during the later stages of the reaction on the morphology of C@Fe3O4 crystal particles. (See also...) Figure 8 As shown, (a1) and (a2) are SEM images of C@Fe3O4 crystal particles from Example 12, (b1) and (b2) are SEM images of C@Fe3O4 crystal particles from Example 13, (c1) and (c2) are SEM images of C@Fe3O4 crystal particles from Example 14, and (d1) and (d2) are SEM images of C@Fe3O4 crystal particles from Example 15. Figure 8It can be seen that when the pH value of the reaction in the later stage is controlled in the range of 10-11, the crystal particle size is small, the distribution is uniform, and the structure is clear.

[0083] Examples 16-20 study the influence of more accurate pH value control of the reaction in the later stage between 10-11 on the crystal particle morphology of C@Fe3O4. See Figure 9 shown, wherein (a) is the SEM image of the C@Fe3O4 crystal particles of Example 16, (b) is the SEM image of the C@Fe3O4 crystal particles of Example 17, (c) is the SEM image of the C@Fe3O4 crystal particles of Example 18, (d) is the SEM image of the C@Fe3O4 crystal particles of Example 19, and (e) is the SEM image of the C@Fe3O4 crystal particles of Example 20, which are obtained by Figure 9 It can be seen that the pH value of the reaction in the later stage has a more obvious influence on the morphology and size of the crystal, and the morphology of the C@Fe3O4 crystal particles is more ideal when the pH value is close to 10.

[0084] Example 21

[0085] In the carbon source dispersion liquid, the dispersant is sodium carboxymethyl cellulose, and the nanocarbon material is carbon nanotube. In the mother liquor of the carbon source dispersion liquid, the mass fraction of sodium carboxymethyl cellulose is 1.5%, and the mass fraction of carbon nanotube is 8%. The other conditions are the same as those in Example 1.

[0086] Example 22

[0087] In the carbon source dispersion liquid, the dispersant is sodium styrene sulfonate, and the nanocarbon material is graphene. In the mother liquor of the carbon source dispersion liquid, the mass fraction of sodium styrene sulfonate is 1.5%, and the mass fraction of graphene is 8%. The other conditions are the same as those in Example 1.

[0088] Comparative Example 1

[0089] When the content of carbon black in the mother liquor of the carbon source dispersion liquid is 10.0% and the mass fraction of polyvinylpyrrolidone (PVP) is 1%, the carbon content in C@Fe3O4 is very low, only 1%.

[0090] Comparative Example 2

[0091] When the content of carbon black in the mother liquor of the carbon source dispersion liquid is 12.5% and the mass fraction of polyvinylpyrrolidone is 1%, the carbon content in C@Fe3O4 is relatively high.

[0092] Comparative Example 3

[0093] C@Fe3O4 obtained in Example 1, LiOH·H2O (micronized) and Al2O3 (nanoscale) are thoroughly ground into powder, sintered at 500°C for 32h, and the obtained product is named C@Li5FeO4-1.

[0094] Example 23

[0095] The C@Fe3O4 obtained in Example 1, LiOH H2O (micro-powder grade) and Al2O3 (nano grade) were mixed and ground into powder. The first sintering temperature was 500°C, the sintering time was 32h. After the first sintering, the powder was crushed, and then the second sintering was carried out. The second sintering temperature was 490°C, the sintering time was 20h. The powder was crushed again. The obtained powder was mixed with 1% of pitch micro-powder by weight of the powder. Then, the mixture was placed in a tube furnace for final sintering at a temperature of 350°C for 20h. The obtained product was named C@Li5FeO4-2.

[0096] The XRD patterns of C@Li5FeO4 prepared by different sintering methods in Comparative Example 3 and Example 23 are shown in FIG. 2. As shown in FIG. 2, the Li5FeO4 peak of C@Li5FeO4-2 is more prominent, accompanied by the characteristic peak of LiFeO2. By observing the spectrum of C@Li5FeO4-1, it is found that the peak value of C@Li5FeO4 is weak, and the characteristic peak of LiFeO2 is very obvious. This finding shows that in the high-temperature reaction, prolonging the reaction time can promote the phase transition of LiFeO2 to Li5FeO4. In Example 23, two-stage calcination method is used. After high-temperature sintering, the powder is crushed and then sintered again, which helps to mix the unreacted LiOH and LiFeO2 uniformly, thereby achieving better sintering effect. Figure 10

[0097] In addition, the introduction of pitch micro-powder in the sintering process is beneficial to the uniform coating of carbon source on Li5FeO4. The pitch micro-powder as a stabilizer can enhance the thermal stability and hydrophobicity of the material, thereby improving the electrical conductivity and the first charge-discharge efficiency of the material, and enhancing the overall electrochemical performance.

[0098] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description simple, all possible combinations of the technical features in the above-described embodiments are not described, but as long as the combinations of the technical features do not exist contradictory, they should be considered as the scope of the description.

[0099] The above-described embodiments only express several implementation manners of the present application, and the description is more specific and detailed, but it should not be understood as a limitation on the scope of the patent. It should be pointed out that for ordinary skilled in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, which are within the scope of the present application. Therefore, the protection scope of the patent of the present application should be subject to the appended claims.​

Claims

1. A method for preparing a lithium supplement, characterized by, It comprises the following steps: (1) configuring a carbon source dispersion liquid, wherein the carbon source dispersion liquid comprises a dispersant, a nano-carbon material and water, and the pH value of the carbon source dispersion liquid is adjusted to 12-13; (2) under the condition that the temperature of the carbon source dispersion liquid is maintained at 40-60℃, the iron-containing solution and the alkaline solution are simultaneously added dropwise into the carbon source dispersion liquid, when the volume of the consumed alkaline solution accounts for 55%-65% of the total volume of the alkaline solution, the pH value is adjusted to 10-11 by using the iron-containing solution and the alkaline solution, the iron-containing solution and the alkaline solution are continuously added dropwise, after the dropwise addition is completed, impurities are removed and dried to obtain C@Fe3O4; (3) C@Fe3O4, micron-sized LiOH·H2O and nano-sized Al2O3 are uniformly mixed to serve as a precursor, and the precursor is sintered and crushed twice in sequence under the condition of nitrogen protection to obtain a primary powder; (4) a stabilizer is added into the primary powder, and after being uniformly mixed, the primary powder is sintered and crushed to obtain the lithium supplement agent.

2. The method of claim 1, wherein the lithium supplement is prepared by the steps of: The dispersant is at least one of polyvinylpyrrolidone, sodium carboxymethyl cellulose, polymaleic anhydride, polystyrene sodium sulfonate and naphthalene sulfonate sodium salt, and the nano-carbon material is at least one of carbon black, carbon nanotube, porous carbon and graphene. ​ 3. The method for preparing the lithium supplement as described in claim 1, characterized in that, The mass fraction of the dispersant in the carbon source dispersion liquid is 0.05-0.5%, and the carbon content is 1.1%-1.5%.

4. The method for preparing the lithium supplement as described in claim 1, characterized in that, The solute of the iron-containing solution is at least one of iron sulfate, iron nitrate and iron chloride, and the solute of the alkaline solution is at least one of sodium hydroxide, ammonia water and calcium hydroxide.

5. The method for preparing the lithium supplement as described in claim 1, characterized in that, The molar concentration of the iron-containing solution is 1-3 mol / L, the molar concentration of the alkaline solution is 1-3 mol / L, and the volume ratio of the carbon source dispersion liquid, the iron-containing solution and the alkaline solution is 3-10:100:150-280.

6. The method for preparing the lithium supplement as described in claim 1, characterized in that, In the precursor, the molar ratio of Fe in C@Fe3O4 to Li in micron-sized LiOH·H2O is 1:5-5.5; in the precursor, the addition amount of nano-sized Al2O3 is 0.05-0.1%.

7. The method for preparing the lithium supplement as described in claim 1, characterized in that, The temperature of the two times of sintering of the precursor in sequence is 400℃-800℃, and the sintering time is 20-32 hours.

8. The method for preparing the lithium supplement as described in claim 1, characterized in that, The stabilizer is in powder form, the material of the stabilizer is at least one of pitch, phenolic resin, polyethylene glycol resin, needle coke and glucose, and after the stabilizer is introduced, the sintering temperature is 350℃, and the sintering time is 20-24 hours.

9. A lithium supplement, characterized in that It is prepared by using the preparation method in any one of claims 1-8.

10. A lithium-ion battery cathode material, characterized in that, The lithium ion battery cathode material comprises lithium iron phosphate, and the addition amount of the lithium supplement agent is 2-4 wt% based on the lithium iron phosphate.

Citation Information

Patent Citations

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN115295795A

  • Lithium battery anode additive material, preparation method and application

    CN116583965A

  • Preparation method of positive electrode lithium supplement agent with high ionic conductivity

    CN117776272A

  • Carbon-coated lithium-rich oxide, and preparation method therefor and use thereof

    WO2024016445A1